A primary source guide to Portugal - Rose, Elizabeth, 1970- (New York : PowerKids Press, 2004)
Presents a guide to the country of Portugal, and includes general information on its economy, people, geography, history, and government, as well as important vocabulary words.
Where is Portugal? -- Living with the sea -- Romans, Visigoths, and Moors -- The Age of Exploration -- Portugal's colonies -- Changes in government -- Portugal's economy -- Saints' days and pilgrimages -- Portugal today -- Portugal at a glance.
Includes index.
6.1
3-6
Keywords: Portugal -- Juvenile literature; Portugal; Portugal